Student characteristics and substance use as predictors of self-reported HIV testing: the youth risk behavior survey (YRBS) 2013–2015. Issue 6 (3rd June 2022) - Outlaw, Angulique Y.; Turner, Blair; Marro, Rachel; Green-Jones, Monique; Phillips II, Gregory
ABSTRACT: Many adolescents and young adults (AYAs; ages 13–24) are unaware of their HIV status despite participating in behavior that places them at risk for contracting HIV. This study examined possible predictors of self-reported HIV testing for high school students (grades 9–12) who completed the Youth Risk Behavior Survey (YRBS). Three sex-stratified, stepwise multivariable logistic models were used to estimate odds of having received a HIV test being associated with student characteristics and substance use. The likelihood of being tested for HIV was associated with students who were a racial/ethnic minority and age 18 and older. HIV testing was also associated with male students who reported same sex partners (males) or same sex partners (males) and different sex partners (females). Female students who reported same sex partners (females) and different sex partners (males) were more likely to have been tested for HIV. Male and female students were more likely to have been tested for HIV if they reported illicit drug and/or marijuana use, while prescription drug use was also associated with HIV testing for female students. Knowledge of the predictors of HIV testing for adolescents can guide efforts for the effective scale up of testing for this vulnerable population.